Properties of Cement-Based Composites Modified with Magnetite Nanoparticles: A Review - Horszczaruk, Elżbieta (Materials, 2019)
Despite the many available studies on the evaluation of the influence of nanomaterials on the properties of cement-based composites, the effects of some nanoparticles have not yet been fully recognized. Among the unrecognized nanomaterials are magnetite nanoparticles (MN). The literature devoted to this subject is limited. This paper reviews state-of-the-art research carried out on the effect of MN on the properties of cement-based composites. Detailed descriptions of the processing, microstructures (hydration products), properties (hydration, workability, mechanical and functional properties, and durability), and probability applications of MN-engineered cementitious composites are presented. Particular attention has been paid to MN application methods to the cement composite. Finally, the risks, challenges, and future development of MN-modified cement-based composites is discussed.